Preparation and characterization of methyl 2-aminobenzoate gel - เพ็ชร์หัสณะโยธิน กรกฎ; บุญบำรุง ดวงกมล; คางคำ สุภาภรณ์ (Progress in Applied Science and Technology, 2018)
This study investigates the properties of methyl 2-aminobenzoate in gel form by finding the suitable amount and composition of gel preparation. The variables studied were the ratio of distilled water to glycerin at 35: 45.5, 30: 50.5, 25: 55.5, 20: 60.5 and 15: 65.5 respectively. The ratio of carboxymethyl cellulose to hydroxyethyl cellulose at 4:0, 3: 1, 2: 2, 1: 3 and 0:4 respectively. The ratio of methyl 2-aminobenzoate to ethyl alcohol solution at 5:5, 6:4, 7:3, 8:2, 9:1 and 10:0 respectively. The physical property of the gel form is determined by calculating the percentage of syneresis, the percentage of weight loss, the percentage of dimensional stability and the stability. The study found that the amount and composition suitable for gel preparation were the amount of distilled water to glycerin at 25: 55.5 ratio. The amount of carboxymethyl cellulose to hydroxyethyl cellulose at 3:1 ratio, and the ratio of methyl 2-aminobenzoate per alcohol at